ENVIRONMENTAL RISK FACTOR ANALYSIS OF PULMONARY TUBERCULOSIS - Ulva, Fadillah; Hikmi, Nailul (Universitas Airlangga, 2025)
Introduction: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria and often attacks lung tissue. TB is one of the ten highest causes of death worldwide. The death rate of TB in Indonesia reaches 140,000 people per year. In 2020, the highest TB cases in Padang are in the Andalas Public Health Center, which is 106 cases. The spread of TB is closely related to the environmental conditions such as the physical condition of the house. This study aims to determine the environmental risk of pulmonary tuberculosis. Methods: This research was observational research with case-control study design. This research was conducted at Andalas Public Health Center (PHC) on Dec 24, 2022 – Feb 16, 2023. The sampling technique used purposive sampling with ratio 1:1, namely 39 houses with pulmonary tuberculosis and 39 houses without pulmonary tuberculosis. Data collection used observation and interview technique. Independent variable in this research is occupancy density, humidity, ventilation to area ratio, and house lighting and pulmonary tuberculosis as dependent variable. Research instrument in the form of questioner, observation sheet, luxmeter, thermo-hygrometer, and roll-meter. Data analysis used univariate, bivariate, and multivariate. Results: The results showed that occupancy density (OR: 0,267 CI95% 0,051-1,387), humidity (OR:0,661 CI 95% 0,145-3,013), ventilation to area ratio (OR: 0,042 CI 95% 0,007-0,232), and house lighting (OR: 0,183 CI 95% 0,044- 0,759), were related to pulmonary tuberculosis incidence. The multivariate results showed that there was a relationship between house lighting and the incidence of pulmonary tuberculosis after controlling of confounding variables. Conclusions: Occupancy density, humidity, ventilation to area ratio, and house lighting, have been proven to be related to pulmonary tuberculosis incidence. House lighting was the most influential factor of pulmonary tuberculosis in Andalas Public Health Center Working Area. Healthy house needs to encourage to reduce the spreading and the incidence of pulmonary tuberculosis.